Effects of Lower Limb Cycling Training on Different Components of Force and Fatigue in Individuals With Parkinson’s Disease - Lin, Yen-Po; Chen, Rou-Shayn; Chen, Vincent Chiun-Fan; Liu, Chun-Hsien; Chan, Hsiao-Lung; Chang, Ya-Ju (Frontiers in Bioengineering and Biotechnology, 2022)
The strength of lower extremity is important for individuals to maintain balance and ambulation functions. Past studies showed that individuals with Parkinson’s disease suffered from fatigue and strength loss of central origin. The purpose of this study was to investigate the effect of lower extremities cycling training on different components of force and fatigue in individuals with Parkinson’s disease. Twenty-four individuals (13 males, 11 females, mean age: 60.58 ± 8.21 years) diagnosed with idiopathic Parkinson’s disease were randomized into training and control groups. The maximum voluntary contraction force (MVC), voluntary activation level (VA), and twitch force of knee extensors were measured using a custom-made system with surface electrical stimulation. The general, central, and peripheral fatigue indexes (GFI, CFI, PFI) were calculated after a fatiguing cycling protocol. Subjects received 8 weeks of low resistance cycling training (training group) or self- stretching (control group) programs. Results showed that, MVC, VA, and twitch force improved (p<0.05) only in the training group. Compared to baseline, central fatigue significantly improved in training group, whereas peripheral fatigue showed no significant difference in two groups. The cycling training was beneficial for individuals with Parkinson’s disease not only in muscle strengthening but also in central fatigue alleviation. Further in-depth investigation is required to confirm the effect of training and its mechanism on central fatigue.